Defining barriers to implementation of nutritional advice in patients with cachexia. Issue 1 (21st August 2019) - Nasrah, Rima; Van Der Borch, Christina; Kanbalian, Mary; Jagoe, R. Thomas
Abstract: Background: Cancer cachexia is a multidimensional wasting syndrome and a reduced dietary intake is both common and strongly correlated with degree of weight loss. Many patients with cachexia do not achieve recommended dietary intake even after nutritional counselling. Prior reports suggest this is likely due to barrier symptoms, but other potential contributory factors have not been studied in detail. Methods: Dietitian‐assigned barriers to successful nutritional intervention were recorded at each visit in all patients attending a multidisciplinary clinic for management of cancer cachexia. The barriers were grouped into 15 categories and classified as either symptom‐related or not symptom‐related. In addition, symptom scores, dietary intake, and weight change were recorded. Results: Data on 94 new patients showed that 89% of patients had at least one major barrier. Four of the five most common barriers and 65% of all barriers identified were not symptom‐related. Over sequential visits the specific barrier(s) in any one patient changed approximately 50% of the time. However, the presence of barriers did not render patients refractory to nutritional intervention and with intervention from the CNR‐JGH team, mean dietary intake increased significantly. Conclusions: In advanced cancer patients with cachexia, non‐symptom‐related barriers to nutritional intervention are more common than symptom‐related. Barriers are dynamic, and repeated careful evaluation over time is required to achieve optimal impact with nutritional intervention in cancer cachexia. Members of the multidisciplinary team need appropriate expertise to address the barriers identified and achieve optimal results with nutritional intervention.